Geração de resíduos de serviços de saúde no contexto pré e pandêmico no município de Sinop, MT-Brasil - Straub, Maikelin Lessandra (2022)
The management of Health Care Waste (HCW) is a public health issue, since this waste is considered hazardous. The HCW come from human or animal health care activities and are classified into five specific groups, depending on the risks present: Group A (potentially infectious), B (chemical), C (radioactive), D (common) and E (perforating). This study aimed to perform a quantitative evaluation of the generation of hazardous HCW (A, B and E) in the period from 2017 to 2022, in municipal public health facilities in the city of Sinop, Mato Grosso State, as well as an analysis of the impact of the Pandemic COVID-19 on their generation. The generation data of 46 health establishments were initially surveyed, from which eighteen Basic Health Units (BHUs) were subsequently selected. From these, the number of procedures performed was obtained. The results showed that the annual mass of HCW generated was variable and with a tendency to increase over the years, with values between 16 to 28 t. The number of procedures in BHUs for the year 2020 was lower than the value for the years 2018, 2019, 2021 and 2022. The mass of waste generated per procedure indicated average values for the year 2020 of approximately 0.22 kg/procedure, compared to values of 0.022 to 0.027 for the other years. The municipal per capita waste generation in BHUs showed variable values throughout the years, in the range of 0.03 to 0.055 kg/inhabitant. The composition of HCW generated in BHUs indicated that the largest percentage of waste generated between 2019 and 2022 are infectious (72 to 82%), followed by perforating-cutting (15.6 to 24.5%) and chemical (between 2 and 3.5%).